Composition and Distribution Characteristics and Geochemical Significance of n-Alkanes in Core Sediments in the Northern Part of the South Yellow Sea - Jinxian He; Shengyin Zhang; Xiaoli Zhang; Yu Qian; Haijun He; Hongchen Wu (Journal of Chemistry)
The South Yellow Sea is an important carbon sink and a significant research area of carbon cycle. After studying the composition and distribution of n-alkanes in a 250 cm long sediment core in the northern part of South Yellow Sea, it can be found that all n-alkanes of sediment samples in this research are distributed in three types, that is, double peak groups, predominance of long-chain n-alkanes, and predominance of short-chain n-alkanes. The average values of ∑C25−35/∑C15−21, ∑C27+29+31/∑C15+17+19, ∑C21-/∑C22+, and (C27+C29+C31+C33)/∑C14–38 are 1.92, 4.22, 0.51, and 0.35, respectively; all above outcomes indicate significant predominance of terrigenous inputs. The average values of C31/C29 and ACL are 1.04 and 29.92, respectively; these results reflect that herbaceous plants and ligneous plants account for similar percentages in the sediment core samples. The average values of CPI1 of short-chain alkanes are 0.80, reflecting the apparent even predominance, which is the result of microbial degradation. The average values of CPI2 of long-chain alkanes of most samples are 2.77, reflecting the apparent odd predominance. The average values of CPI and Pr/Ph, as well as the Pr/nC17 and Ph/nC18 correlation diagram, reflect that the organic matter is immature and suggest reductive sedimentary environment.